De "Itália sergipense" a "relicário de saudade": música em São Cristóvão Provincial (1820-1889) - Thais Fernanda Vicente Rabelo Maciel (2021)
Throughout the 19th century, several capital changes occurred in Brazil, in a context in which the belief in the idea of progress and economic growth opposed the idea of past. In that period, cities such as Recife and Maceió, for example, became new provincial headquarters. The same happened in Sergipe. In the case of São Cristóvão, which would lose the post of capital in 1855, the change of status had a great impact in several areas of that society, including the cultural. Therefore, the objective of this thesis is to understand the impacts of the capital change in musical activity in São Cristóvão through a study on music in the 19th-century São Cristóvão. Our research was based on a bibliographic survey, including writings of memorialists and local historiography, and on an in loco research of spaces such as philharmonic band headquarters and religious temples. The hemerographic and archival researches were also essential and helped us with the understanding of a more cohesive panorama. The variety of sources (which also included musicographic documents, iconography, and poetry) allowed us to cross-reference information and data, forming a broad context rich in details. In addition, discussions encompass instigating aspects such as disagreements over music in the Catholic Church in the mid-19th century and the relationship between music and politics at a national and, especially, local level. The results suggest that the change of the capital city has impacted the musical memory process of São Cristóvão society, contributing to the disappearance of sources, including musical ones. From the investigation, a vast scenario, hitherto unknown, began to be outlined, encompassing the activity of musicians from São Cristóvão in several aspects, scenic spaces, and repertoires. The work also contemplated the edition of two music works related to São Cristóvão, among them, the Motetos dos Passos, a repertoire linked to the tradition of the Procession of Our Lord of the Steps of the old capital, which dates back to more than two centuries, without interruption.